Study the MAG Parameters Influence on Depth Of Penetration of AA-5083 Joint – A Review - Lakshman Singh, Amrinder Singh (International Journal of Advanced Science and Technology, 2020)
Active Gas (MAG) welding has high quality for joining two or more materials efficiently. AA-5083 grade is selected on the basis of important factors such as corrosion resistance, fabrication, heat treating good combination of toughness and formability. MAG is efficient welding utilized in aerospace, ship & marine industries. In this research, measure the speed, shield gas and heat influence on depth of penetration of AA-5083 joints with size of 45 mm x 40 mm x 4 mm. In this, maximum penetration depth 4.59 mm measured for speed 146.48 mm/ min, shielding gas 12.45 Lt/ min & heat 1937.47 J/ mm with constant voltage 22 volt & current 215 amps.